Toxicological assessment of crude palm oil (Elaeis guineensis Jacq.) used in deep frying of akara (cowpea paste finger food) - I. Felzenszwalb; J. L. da Costa Mazzei; S. Feitosa; C. A. Fortes Aiub; D. T. de Almeida (Grasas y Aceites, 2014)
Akara is cowpea paste which is deep-fried in crude palm oil (CPO; Elaeis guineensis Jacq.) and sold as a street finger food in Brazil and Africa. During the food frying oils can form toxic decomposition products as total polar compounds (TPC), which can determinate oil degradation. The aim of this study was to assess the toxicity of CPO used in akara frying for 25 hours. Changes in the oil were determined by TPC quantification and mutagenicity using a Salmonella/microssome assay with Salmonella Typhimurium strains TA97, TA98, TA100 and TA102 with and without exogenous metabolic activation. Assuming that 25% TPC is the maximum level permitted in frying oils and it ranged from 14.08 to 29.81%, frying palm oil exceeded the limit. Nonetheless, no cytotoxic, mutagenic or genotoxic activity were detected in CPO used in the traditional akara frying process.